Manual Labour, Intellectual Labour and Digital (Academic) Labour. The Practice/Theory Debate in the Digital Humanities - Christophe Magis (tripleC: Communication, Capitalism & Critique)
Although it hasn’t much been considered as such, the Digital Humanities movements (or at least the most theoretically informed parts of it) offers a critique “from within” of the recent mutation of the higher education and research systems. This paper offers an analysis, from a Critical Theory perspective, of a key element of this critique: the theory vs. practice debate, which, in the Digital Humanities, is translated into the famous “hack” versus “yack” motto, where DHers usually call for the pre-eminence of the former over the latter. I show how this debate aims to criticize the social situation of employment in academia in the digital age and can further be interpreted with the Cultural industry theoretical concept, as a continuance of the domination of the intellectual labour (ie. yack in this case) over the manual labour (hack). Nevertheless, I argue that, pushing this debate to its very dialectical limit in the post-industrial academic labour situation, one realizes that the two terms aren’t in opposition anymore: the actual theory as well as the actual practice are below their very critical concepts in the academic labour. Therefore, I call for a reconfiguration of this debate, aiming at the rediscovering of an actual theory in the academic production, as well as a rediscovering of a praxis, the latter being outside of the scientific realm and rules: it is political.